Pro-environmental behaviour among primary school children in the West Coast of Sabah, Malaysia - Wong, Charmaine Andrea (2018)
Environmental Education has been part of the primary school curriculum for over thirty years. The aim of Environmental Education is to develop students who are environmentally literate and ultimately behave pro-environmentally. To date, studies among primary school students which include all four components of the environmental literacy domain has not been carried out in Sabah. Therefore there is an urgent need to assess the state of proenvironmental behaviour among primary school students, as well as the factors which affect pro-environmental behaviour of students. The purpose of this study was to analyse the pro-environmental behaviour of primary school children in the West Coast of Sabah, based on the Theory of Planned Behaviour (Ajzen, 1985), and the components of the domains of EL (McBeth et al., 2011). The factors measured in this study included ecological knowledge, disposition towards the environment, competencies in identifying environmental issues and action strategy skills possessed by the primary school children. Furthermore, the influence of various student characteristics upon the proenvironmental behaviour of primary school children was also determined. These student characteristics included gender, race, pre-school attendance, involvement in after school clubs, and leadership roles. The design of this study was a quantitative survey among primary school students within six districts in the West Coast of Sabah. The factors affecting pro-environmental behaviour among 1025 Year 5 students from 17 national primary schools along the West Coast of Sabah, was determined using a primary School Environmental Literacy Instrument (PSELI) that was completed by the Year 5 students of each school. Interviews with key personnel involved in environmental education in the school, as well as on site observation of evidence promoting pro-environmental behaviour were also carried out. The Primary School Environmental Literacy Instrument was adapted and modified to suit the local Year 5 students, and included eight parts with a total of 68 items. These questions included multiple choice, as well as 5 point Likert scale items. The data collected was analyzed using SPSS (Statistical Package for Social Sciences v.22). An Exploratory Factor Analysis was used to determine the disposition dimensions of the primary school students. A Multiple Linear Regression was carried out to determine the significant factors influencing pro-environmental behaviour of students. The findings revealed that the students had a moderate level of environmental literacy and ecological knowledge, while the level of competency in issue identification and action strategy planning was low, whereas their disposition and pro-environmental behaviour scores ranged between moderate to high. Furthermore, the findings from the Multiple Linear Regression analysis indicated that 8 predictor variables significantly influence the pro-environmental behaviour of primary school students in the West Coast of Sabah. These included 6 disposition related variables, competency in action strategy planning, and gender variables. The findings of this study have contributed to research and literature in environmental education, and environmental literacy, in particular as existing research often exclude environmental issue investigation, and proenvironmental behaviour among younger students. Research findings will also help environmental education providers, policy and curriculum developers to gauge the extent to which the current environmental education program in Sabah has met the aims of the Malaysian Education Ministry, in creating environmentally literate students. Consequently, understanding the factors affecting students’ pro-environmental behaviour will allow them to better provide for the environmental literacy needs of different groups of students. This study has highlighted the urgent need to improve the competency level among primary school students, as well as to provide meaningful and effective environmental education programs for boys. Furthermore, this study has also contributed to current practice in the implementation of environmental education across the curriculum, by highlighting the importance of hands-on gardening and environmental activities in natural settings, in the development of pro-environmental behaviour.